The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5455/2320-6012.ijrms20150120
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Severity, Prognostic Significance of Thrombocytopenia in Malaria

Abstract: The word "malaria" comes from the Italian, and means literally 'bad air'. Malaria remains today as it has been for centuries, a heavy burden on tropical communities, a threat to non-endemic countries, and a danger to travelers. Malaria ranks third among the major infectious diseases in causing death. Malaria is an infectious disease caused by plasmodium parasite. Plasmodium vivax, P. falciparum, P. ovale, P. malariae and P. knowlesi. 1 are the different species. P. falciparum account for majority of morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…21,23 These findings were comparable to the study conducted by Dharmesh Kumar N Patel et al, in which complicated malaria was more commonly caused by falciparum malaria and was rarely caused by other malarial parasites. 26 Kocher et al, Bezwada Srinivasa Rao et al,Sudheer Babu Devineni et al, they all observed that P. Falciparum infection was to be predominantly associated with complicated malaria and P.Vivax was more associated with uncomplicated malaria.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…21,23 These findings were comparable to the study conducted by Dharmesh Kumar N Patel et al, in which complicated malaria was more commonly caused by falciparum malaria and was rarely caused by other malarial parasites. 26 Kocher et al, Bezwada Srinivasa Rao et al,Sudheer Babu Devineni et al, they all observed that P. Falciparum infection was to be predominantly associated with complicated malaria and P.Vivax was more associated with uncomplicated malaria.…”
Section: Resultssupporting
confidence: 81%
“…22 Later in 2015 Bezwada Srinivasa Rao et al also supported the present study with similar results showing 61% cases suffering from P.Vivax malaria, 35% cases had P. Falciparum malaria and 4% had mixed infection. 23 Present and above mentioned studies showed that P.Vivax malaria was more common among all malaria cases. Prevalence of P.Vivax malaria is common in India because of variations in climatic condition and breeding places of mosquito and genetic resistance of P. Falciparum.…”
Section: Resultsmentioning
confidence: 87%
“…Present study was nearly similar to study done by Raoet BS al reported complicated malaria in 17 cases (18.89%) and uncomplicated malaria in 73 cases (81.11%). 26 In present and above study, uncomplicated cases were more than complicated cases because of P. Vivax species was common infection.…”
Section: Discussionmentioning
confidence: 96%
“…Later in 2015 Bezwada Raoet S al also supported the present study with similar results showing 61% cases suffering from P. Vivax malaria, 35% cases had P. Falciparum malaria and 4% had mixed infection. 23,26,28 In present study fever was the commonest clinical manifestation present in 100% cases followed by nausea vomiting in 52%, headache in 34%, myalgia in 28%, jaundice in 27%, diarrhoea in 20%, oliguria in 10%, pain abdomen in 07%, impaired consciousness in 04%, cough and breathlessness in 05% and joint pain in 5% cases. 23 Present study's results are nearly similar to study done by Gopinath VP et al reported fever in 97.8% and vomiting in 42.2%, headache in 69%, altered sensorium in 8.8% cases, Murthy GL et al who also reported fever with chills and rigor in 98.10%, altered sensorium in 48.10%, headache in 33.40%, diarrhoea in 18.35%, jaundice in 27.21% and oliguria in 6.96% cases, later Madhu Muddaiah et al noticed that fever was present in all cases (100%), nausea and vomiting in 37.36%, headache in 33.6%, jaundice in 15.78%, altered level of consciousness in 4.21% cases, and even Sudheer Babu Devineni et al also noted that fever was the most common symptom (100%) followed by vomiting in 22.22%, headache in 25.56%, jaundice in 15.56%, altered sensorium in 8.89%, pain abdomen in 7.77%, cough and breathlessness in 4.44%, and joint pain in 5.56%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation